Stealth RF energy harvesting in MRI using selective shielding - Bjorkqvist, Oskar; Pruessmann, Klaas P. (Magnetic resonance in medicine, 2024)
Purpose To utilize the transmit radiofrequency (RF) field in MRI as a power source, near or within the field of view but without affecting image quality or safety. Methods Power harvesting is performed by RF induction in a resonant coil. Resulting RF field distortion in the subject is canceled by a selective shield that couples to the harvester while being transparent to the RF transmitter. Such shielding is designed with the help of electromagnetic simulation. A shielded harvester of 3 cm diameter is implemented, assessed on the bench, and tested in a 3T MRI system, recording power yield during typical scans. Results The concept of selective shielding is confirmed by simulation. Bench tests show effective power harvesting in the presence of the shield. In the MRI system, it is confirmed that selective shielding virtually eliminates RF perturbation. In scans with the harvester immediately adjacent to a phantom, up to 100 mW of average power are harvested without affecting image quality. Conclusion Selective shielding enables stealthy RF harvesting which can be used to supply wireless power to on‐body devices during MRI.